Hubungan Tingkat Pengetahuan Peserta JKN dengan Pemanfaatan Mobile jKN - Herlinawati; Heni Far'iatul Aeni; Iis Priatnaningsih; Dewi Ratnawati (Optimal Midwife Journal, 2026)
Mobile JKN is a digital breakthrough created by Social Security Agency for Health (BPJS) to provide health service that are more eficient, transfarant and based on the needs of National Health Insurance (JKN) participants. Currently, JKN in membership in Indonesia Reached 97,9%. However, mobile JKN  aplication users only reached  17,8% of the total number of the JKN participant. Based on preliminary studi conducted in November 2025, it was found  that 6 outnof 10 JKN participant who visited did not use the mobile JKN aplication. Most people didn't know about the mobile JKN application. This study aim to determine the correlation between the level of knowledge of JKN participation and the use of mobile JKN. It was a quatitative study with crossectional design. The studi population involved JKN participants registered as many as 15.521 people. The sample size was determined at 100 respondents by using the accidental sampling methode. Data were collected throught a questionnaire and observations. The data collection instrumen used here wewr questionnaire and observation sheet.  Data were analyzed using the square test. The study findings revealed a significant correlation between the level of knowledge of JKN participant and the use of mobile JKN,. Based on study result, there is a need for efforts to increase the knowledge of JKN participant throught education or by updating information on the mobile JKN application throught video broadcast on audio visual media (television) installed at the patient waiting (registration) room. Furthermore, healthcare workers are expected to assist and guide the JKN participation to use the features of the Mobile JKN application.